Corrosion Performance and Rust Conversion Mechanism of Graphene Modified Epoxy Surface Tolerant Coating - Guo, Xiaoping; Xu, Hao; Pu, Jibin; Yao, Chao; Yang, Jing; Liu, Shuan (Frontiers in Materials, 2021)
A graphene modified epoxy surface tolerant coating was prepared, and the corrosion performance and rust conversion mechanism of the prepared composite coating on rusty carbon steel substrate was investigated. SEM, XRD and IR spectrum were used to confirmed the iron rust conversion performance by the reaction of phytic acid and rust. EIS, polarization curve and salt spray test were used to evaluate the corrosion resistance of low surface treatment coatings . Results indicated most of the rust were dissolved and transformed with the reaction of phytic acid and rust on the rusty carbon steel, graphene could effectively improve the compactness and protective performance of the epoxy surface tolerant coating.